O Anel do Imperador (1934), de João dos Reis Gomes, entre a História e a Ficção: Napoleão e a Madeira - Paulo Miguel Rodrigues (Carnets, 2012)
The Emperor's Ring (1934) reminds us - linking them - two historic moments involving Napoleon and Madeira: first, his passage through the bay of Funchal, in August 1815, in his path to exile; a quarter century later, in July 1840, the passage at the same place, of the French frigates La Belle Poule and Favorite, also directed to St. Helena, under the command of the Prince of Joinville, now with the mission of transporting the former emperor’s remains back to France. From these two facts - and referring to some of the historical personalities involved in them - fiction and history intersect in the work of João dos Reis Gomes.